The contribution of paraoxonase 1 and myeloperoxidase to HDL-cholesterol functionality - Malara Marzena; Kęska Anna; Lutosławska Grażyna (Sciendo, 2016)
The purpose of this study was to analyse the scientific evidence concerning the effects of two enzymes - paraoxonase 1 and myeloperoxidase - on the functions of HDL-cholesterol. It is well documented that disturbed circulating lipoproteins (a high total and high LDL-cholesterol, and low HDL-cholesterol) bring about atherosclerosis and an increased risk of cardiovascular disease (CVD) which is recognised as the main cause of death all around the world. In consequence, numerous studies have focused on procedures which will improve the plasma lipoproteins profile by decreasing the total cholesterol and the LDL-cholesterol (LDL-C) and increasing the HDL-cholesterol (HDL-C). However, the anti-atherogenic role of HDL-C has been challenged in studies showing that genetically elevated HDL-cholesterol does not offer protection against CVD. Moreover, it has been found that raising the circulating HDL-cholesterol fails to reduce atherosclerosis. The doubts concerning the protective role of HDL-C have been supported by in vitro studies which indicate that the HDL-C from patients with atherosclerosis does not have a protective action, but does stimulate inflammation and free radical synthesis. The above data suggests that HDL-C, commonly recognised as protective against atherosclerosis, in some circumstances becomes pro-atherogenic, and is thus dysfunctional. Our review focuses on two enzymes - paraoxonase 1 (PON1) and myeloperoxidase (MPO) - which markedly affect the properties of HDL-C and contribute to its anti - or pro-atherogenic activity. Moreover, the effects of the diet and physical activity on PON1 and MPO are summarised with respect to the HDL-C functionality.